Role of zakat to eradicate poverty in Malaysia - Mohd Rodzi Embong; Roshaiza Taha; Mohd Nazli Mohd Nor (Penerbit Universiti Kebangsaan Malaysia, 2013)
This paper discusses the role of zakat as a mechanism for poverty eradication. Zakat is defined as ‘purification’ or ‘growth’. Zakat enables the wealthy or rich people to purify their hearts from greed by giving a part of their wealth to the needy. The needy who receive the zakat are then able to fulfil their needs, and, thus, the economic wealth bestowed by Allah s.w.t is spread to all the people and real economic growth is achieved. Zakat, if managed effectively and efficiently, should be able to reduce the gap between the rich and the poor. Each year, the annual reports of zakat institutions in Malaysia highlight the significant increase in zakat collection. Does the increase in zakat collection contribute to the alleviation of poverty in Malaysia? To find answers to this question, this paper observes the trend of zakat collection and analyses the pattern of zakat distribution. It is hoped that the outcome of this discussion will contribute to a better understanding of zakat management relative to its role as a tool for poverty eradication.